Penggunaan Teknik Role Playing and Modeling untuk Meningkatkan Keterampilan Komunikasi Interpersonal Peserta Didik - Risky Desi Permatasari; Asrowi Asrowi; Edy Legowo (Jurnal Psikoedukasi dan Konseling, 2022)
Abstract: This research aims to obtain data related to the Use of Role-Playing and Modeling Techniques to Improve Students' Interpersonal Communication Skills. The research method used is library research. The data analysis technique used is the content analysis reviewed from several references and literature. The results showed increased students' interpersonal communication skills after the intervention. This is evidenced by (1) The theoretical basis; (2) Purpose of use; (3) the successful use of role-playing and modeling techniques; (4) Implementation procedure; (5) The technique used; (6) learning objectives; (7) Recommendations for the use of role-playing techniques; (8) The relationship between the use of role-playing and modeling techniques in improving interpersonal communication skills by imitating and playing role play until these skills increase so that over time it will shape individual traits and behavior.Abstrak: Tujuan penelitian untuk mendapatkan data terkait Penggunaan Teknik Role Playing dan Modeling untuk Meningkatkan Keterampilan Komunikasi Interpersonal Siswa. Metode penelitian yang digunakan adalah penelitian kepustakaan. Teknik analisis data yang digunakan adalah analisis isi yang ditinjau dari beberapa referensi dan literatur. Hasil penelitian menunjukkan adanya peningkatan kemampuan komunikasi interpersonal siswa setelah dilakukan intervensi. Hal ini dibuktikan dari (1) Landasan teori; (2) Tujuan penggunaan; (3) Keberhasilan penggunaan teknik role playing dan modeling; (4) Prosedur pelaksanaan; (5) Teknik yang digunakan; (6) Sasaran belajar; (7) Rekomendasi penggunaan teknik role playing; (8) Hubungan penggunaan teknik role playing dan modeling dalam meningkatkan keterampilan komunikasi interpersonal dengan meniru dan memerankan role play sampai keterampilan tersebut meningkat sehingga lama kelamaan akan membentuk sifat dan perilaku individu.